Edukasi Terapi Air Rebusan Daun Salam Untuk Menurunkan Kadae Asam Urat Pada Anggota Keluarga Tn.R Dengan Gout Arthritis di Desa Tlahab Lor - Helmi H; Eko Sari Ajiningtyas; Wiwik Priyatin (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Background: Based on data from health cadres in the Rw 01 Tlahab Lor Village area in 2022, the uric acid rate reached 41.11%. Uric acid is the final metabolic product of purines, which is a component of nucleic acids found in the nucleus of body cells. One of the treatments to increase knowledge is by providing education about non-pharmacological therapy is using bay leaf boiled water to reduce uric acid levels. In preclinical trials, a dose of 20 mg/200 gram BW of bay leaves was able to reduce blood uric acid levels equivalent to synthetic allopurinol at a dose of 2.7 mg/kg BW. Purpose: This study was to increase family knowledge after being given education and to prove the therapy of bay leaf boiled water on uric acid levels. Research Method: This study used the case study method with family respondents with gout focusing on increasing family knowledge by providing educational education on bay leaf boiled water therapy. Using 3 instruments, namely observation sheets, interview sheets and the format of assessment of family nursing care. This research was conducted for 7 visits a week, namely on March 22-28 2023. Results: after implementation, the level of family knowledge about gout arthritis which previously had a low score (50) became very good with a score of 94. Conclusion: by providing education to families, family knowledge becomes understandable and can apply gout arthritis treatment with bay leaf boiled water therapy. So that it can change the ability of families to care for sick family members.